Problématiser et modéliser pour appréhender le chocolat comme objet d'investigation complexe à l'école maternelle - Bertrand Gremaud; Justine Letouzey-Pasquier; Patrick Roy; Alexandre Mauron (Université de Provence, 2022)
An analysis of teaching practices highlighting the central role of modelling when combining a Socially Vital Issue (SVI), "Chocolate", (Simonneaux & al., 2017) and the development of complex thinking skills. This article reports how two kindergarten teachers applied the modelling process through an interdisciplinary investigative approach (Roy and Gremaud, 2017) to capture the complexity (Hertig, 2018) of a commonplace (concrete world) subject, "chocolate", by transforming it into an interdisciplinary investigative subject (conceptual world). The chocolate industry, a subject of study at times controversial due to its modes of consumption and its production chain, was approached in the classroom with the objective to form future reflective and critical thinking citizens. The creation of an Interdisciplinary community of Practice and Discourse (Roy, Gremaud and Jenni, in press) was present to support the two educators. It focused upon two didactic concepts: the interdisciplinary investigative approach and the modelling of complex thinking.